2018
DOI: 10.1002/smi.2800
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality is associated with increased desire for alcohol in response to acute stress

Abstract: Type D personality (the combination of negative affectivity and social inhibition) is associated with high levels of alcohol consumption. We examined if Type D was associated with higher levels of alcohol use, and if Type D was associated with desire for alcohol in response to a social stressor. In an experimental study, participants (n = 138) completed measures of Type D, stress, and alcohol use. They also took part in a stress-inducing public speaking task and provided measures of desire for alcohol at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…15 Williams et al reported Type D individuals exhibited significantly higher levels of desire for alcohol during the acute stress and recovery phases, compared to non-type D individuals. 16 Williams et al suggested that type D individuals might be motivated to consume alcohol in order to cope with stressful situations. 16 Therefore, type D dental students should be provided more emotional and psychological supports to prevent depression and alcoholism among them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Williams et al reported Type D individuals exhibited significantly higher levels of desire for alcohol during the acute stress and recovery phases, compared to non-type D individuals. 16 Williams et al suggested that type D individuals might be motivated to consume alcohol in order to cope with stressful situations. 16 Therefore, type D dental students should be provided more emotional and psychological supports to prevent depression and alcoholism among them.…”
Section: Discussionmentioning
confidence: 99%
“…16 Williams et al suggested that type D individuals might be motivated to consume alcohol in order to cope with stressful situations. 16 Therefore, type D dental students should be provided more emotional and psychological supports to prevent depression and alcoholism among them.…”
Section: Discussionmentioning
confidence: 99%
“…One could argue that the scores were meancentered and the authors forgot to report it, but there are in fact several reasons to assume that raw scores rather than centered scores were used. First, several studies report the correlations between NA, SI and their product score [26,31,33]. If NA and SI would have been mean-centered before multiplying them, these raw scores would barely correlate with their multiplication.…”
Section: Appendix B Important Excluded Studiesmentioning
confidence: 99%
“…However, in some of these studies the bivariate correlation between both traits and the dependent measure were reported. For instance, Williams and colleagues [33] showed that the product of NA and SI was positively correlated with alcohol dependence. However, the bivariate correlations also indicate a significant positive correlation for SI with alcohol dependence, while the correlation with NA is very weak and not statistically significant.…”
Section: Appendix B Important Excluded Studiesmentioning
confidence: 99%
“…However, with regard to people with alcohol addiction, some researches have found the link between personality type D and addiction (16,17). This stress-prone personality is characterized by negative affect and social inhibition.…”
Section: Introductionmentioning
confidence: 99%